Cómo construir una marca personal potente - Reyes, Raiza (2021)
Raiza Reyes (Perú) - Moderadora; Katherine Muñoz (Perú) - Expositora; Patricia Meza (Perú) - Moderadora; Clara Espinoza (Perú) - Moderadora